The psychology of attention - Pashler, E. Harold (Cambridge MIT Press, 1998)
1. Introduction --2. Selective attention --3. Divided attention --4. Attentional set --5. Capacity and selection : theorizing about attention --6. Central processing limitations in sensorimotor tasks --7. Attention and memory --8. Automaticity, effort, and control.